Working together to train child welfare workers on the impact of domestic violence on children: A faculty-staff collaborative research project - Andrea Nikischer; Jeanette Koncikowski (Adult Education Research Conference, 2015)
This presentation will discuss the “Research in Domestic Violence for Child Welfare Trainers and Case Workers" collaborative “match” project. This project featured the pairing of a SUNY Buffalo State faculty member with an education specialist from the Institute for Community Health Promotion. Research findings will be shared.
Keywords: collaborative research; E-learning; domestic violence